The Risk Factors Burnout among Nurses in General Hospital Kebumen - Irawan, Hendi; Soleman, Sani Rachma; Jamil, Nur Aisyah (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2019)
Background: Burnout is a collection of symptoms due to a usage of energy generating physically, mentally and emotionally exhausted which is affecting health care workers in hospital particularly nurse. The objective of this research is to understand the risk factors of burnout among nurses in general hospital Kebumen, Central Java Province in Indonesia. Method: A cross-sectional study was conducted as a research design. About 125 samples had selected with consecutive sampling as a method to collect respondents. There were five independents variables such as ages, length of work, gender, education background and marital status, yet burnout as a dependent variable. This research was analyzed by chi-square for bivariate and logistic regression technique for multivariate. Results: According chi-square test explained that variables age (p-value 0.052, OR 2.276 and CI 95% 0.984-5.263, education (p-value 0.511, OR 0.759 and CI 95% 0.333-1.729, light of work (p-value 0.159, OR 0.551 and CI 95% 0.239-1.270), gender status (p-value 0.987, OR 1.007 and CI 95% 0.440-2.306) and marital status (p-value 0.868, OR 0.926 and CI 95% 0.377-2.277) that concluded none of those variables had correlated to burnout among nurses in general hospital, Kebumen District, Indonesia. However, logistic regression was attained only age of respondents as a significant variable against burnout (p-value 0.029, OR 2.634, CI 95 % 1.101-6.298). Conclusion: Based on this research had identified that age >35 years old is the most affecting predictor against burnout among nurses in general hospital Kebumen, Central Java Province, Indonesia.